Pengaruh Penggunaan Aplikasi Zoom Meeting Terhadap Kemampuan Pemecahan Masalah Matematika Siswa Pada Pembelajaran Daring Di Kelas V - Gita Ramadayanti; Khaola Rachma Adzima (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
The purpose of this study is to explore the influence of the use of zoom meeting applications on students' math problem-solving skills in online learning in class V. The method in this study uses survey methods. The sample in this study was all VA SDN Duri Kepa 05 students as many as 30 students. Instruments to collect data used in this study are the use of zoom meeting applications and tests of students' math problem-solving skills. The results of the study obtained using a partial test (t) that showed that a significant 0.00 < 0.05. These results showed H0 was rejected and H1 accepted, meaning there was a significant influence between the use of zoom on students' problem-solving abilities.